MANAJEMEN KURIKULUM PROGRAM BASIC TECHNOLOGY EDUCATION DI SMP AL KAUTSAR BANDAR LAMPUNG - Martira Putri; Sumadi sumadi; Supomo Kandar (Program Studi Magister Manajemen Pendidikan)
This research aimed to develop curriculum management of Basic Technology Education Program in SMP Al Kautsar Bandar Lampung. This research used qualitative approach with data collection techniques was using interviews, observation, and documentation. Data were analyzed by using the patterns modification of interaction of Miles and Huberman. The result showed that curriculum planning refers to social forces, treatment knowledge, and human growth and development; organizing philosophy and the nature of knowledge, society and culture, the individual, and learning theory; implementation of curriculum characteristics, implementation of strategies, characteristics of assessment, teacher's knowledge about curriculum, attitudes toward curriculum, and directing skills are referenced in curriculum; supporting is full of facilities and infrastructure required, whereas the inhibitors is the paradigm of the students who are still narrow, and time is still lacking; and evaluation components of the needs analysis and feasibility studies, planning and development, learning processes, curriculum revision, and research curriculum.Penelitian ini bertujuan mengembangkan manajemen kurikulum program Basic Technology Education di SMP Al Kautsar Bandar Lampung. Penelitian menggunakan pendekatan kualitatif, teknik pengumpulan data dengan wawancara, observasi, dan dokumentasi. Teknik analisis data menggunakan pola modifikasi interaksi Miles dan Huberman. Hasil penelitian diperoleh bahwa perencanaan mengacu pada kekuatan sosial, perlakuan pengetahuan, serta pertumbuhan dan perkembangan manusia; pengorganisasian philosophy and the nature of knowledge, society and culture, the individual, dan learning theory; implementasi karakteristik kurikulum, strategi implementasi, karakteristik penilaian, pengetahuan guru tentang kurikulum, sikap terhadap kurikulum, dan keterampilan mengarahkan;. penunjangnya lengkapnya sarana dan prasarana yang dibutuhkan, penghambatnya waktu yang masih kurang; dan evaluasi komponen-komponen analisis kebutuhan dan studi kelayakan, perencanaan dan pengembangan, proses pembelajaran, revisi kurikulum, dan research kurikulum.Kata kunci: Manajemen, kurikulum, basic technology education